Effect of acupuncture at Zusanli (ST36) point on antral contraction function under ultrasound guidance: study protocol of a randomized controlled trial - Yingqi Chen (BMC, 2021)
Abstract Background Although the relationship between deqi sensations and curative effect has always been controversial, deqi sensations has been regarded as the key indicator of clinical efficacy of acupuncture therapy. There is little evidence for standardization or visualization of the mechanism of acupuncture’s therapeutic effect. This trial aims to evaluate the effect of needling at Zusanli (ST36) on antral contraction function as visualized by ultrasound. Methods This is a two-arm, single-blind, randomized, controlled trial. A total of 116 acupuncture-naïve healthy subjects will be randomly allocated to the acupuncture group or sham acupuncture group in a 1:1 ratio. Participants in the acupuncture group will receive manual acupuncture at Zusanli (ST36) with the needling depth at crural interosseous membrane. Those in the sham acupuncture group will be given penetrating needling depth at the superficial fascia layer. The primary outcome will be the changes in antral contraction frequency (ACF) before and after acupuncture. The secondary outcomes will be the changes in the thermal infrared spectrum of gastric area skin, the antral contraction amplitude (ACA), the antral movement index (AMI), and the scores on the Chinese version of Massachusetts General Hospital Acupuncture Sensation Scale (C-MASS). The adverse events will be evaluated and recorded in detail. Discussion This study may provide visual and objective evidence regarding the safety and efficacy of manual acupuncture at Zusanli (ST36). In addition, the results of this study will help to identify the role of Zusanli (ST36)in the inducing deqi. Trial registration Chinese Clinical Trial Registry ChiCTR2000040686 . Registered on 8 December 2020